Photophysicochemical and photodynamic studies of phthalocyanines conjugated to selected drug delivery agents,Photophysicochemical and phototherapeutic studies of phthalocyanines conjugated to selected drug delivery agents - Nombona, Nolwazi (Rhodes University, Faculty of Science, Department of Chemistry, 2012)
This work reports on the successful synthesis, characterisation and photophysical properties of new asymmetric metal free, magnesium and zinc phthalocyanines. The synthesis of symmetrical phthalocyanines is also reported. A selection of phthalocyanines have been conjugated, covalently linked, encapsulated or mixed with selected of drug delivery agents which include gold or silver nanoparticles, poly-L-lysine, liposomes and folic acid. The influence of delivery agent on the photophysical and photochemical properties of conjugated phthalocyanine is investigated. The studies showed that the Au nanoparticle significantly lowered the fluorescence quantum yield values of the phthalocyanines. The photodynamic activity of Zn phthalocyanine-Îµ-polylysine conjugates in the presence of nanoparticles towards the inactivation of Staphylococcus aureus showed high photoinactivation in the presence of silver nanoparticles. The presence of silver nanoparticels from the minimal inhibition concentration (MICâ‚…â‚€) studies showed remarkable growth inhibition for the tested conjugates even at low concentrations. The conjugate also showed no dark toxicity when evaluated using the chick choriallantoic membrane (CAM) assay. The efficiency of selected zinc phthalocyanine as photodynamic therapy (PDT) agents was investigated. The production of reactive oxygen species (ROS) and phototoxicity of the photosensitizers were assessed. Healthy fibroblast cells and breast cancer (MCF-7) cells were treated with either free phthalocyanine or phthalocyanine bound to either gold nanoparticles or encapsulated in liposomes. Cell viability studies showed the optimum phototoxic effect on non-malignant cells to be 4.5 J.cmâ »Â². The PDT effect of the liposome bound phthalocyanine showed extensive damage of the breast cancer cells. Gold nanoparticles only showed a modest improvement in PDT activity.
Keywords: Phthalocyanines; Photochemistry; Photochemotherapy; Drug delivery systems; Magnesium; Zinc; Nanoparticles; Staphylococcus aureus